A comparative study of terpene composition in different clades of the genus Lavandula. Issue 3 (2nd October 2018) - Guitton, Yann; Nicolè, Florence; Jullien, Frédéric; Caissard, Jean-Claude; Saint-Marcoux, Denis; Legendre, Laurent; Pasquier, Bernard; Moja, Sandrine
ABSTRACT: The genus Lavandula L. (Lamiaceae) comprises 40 species, of which only a few are used to extract essential oils for perfume and detergent industries. To date, the compound diversity of Lavandula essential oils, and most notably terpene variation amongst species, is poorly documented. In this work, we report the diversity of terpene content in 33 accessions from the subgenera Lavandula and Fabricia . We used these terpenes to distinguish subgenera and sections and to find autapomorphic and synapomorphic traits as taxonomic markers. We demonstrate that terpene composition is not appropriate for phylogenetic reconstruction and chemotaxonomy in Lavandula, but we show nevertheless that terpene diversity allow for distinguishing the two subgenera, Lavandula and Fabricia and for separating the sections, respectively i/Dentatae, Stoechas and Lavandula, and ii/Pterostoechas, Chaetostachys, Subnudae and Hasikenses . Furthermore, amongst terpenes with putative ecological roles, we found that camphor, 1, 8-cineole and carvacrol are synapomorphic traits, or at least markers respective of each subgenus, that trans -α-necrodol is an autapomorphic trait of L. stoechas subsp. luisieri and that linalool is either a symplesiomorphic trait or a homoplasic trait. Based on these results, we propose evolutionary hypotheses and future work directions relative to the putative ecological role of these terpenes in other species and to terpene biosynthesis studies in Lavandula .